Impact Of Transurethral Resection Of Prostate On International Prostate Symptom Score And Peak Urinary Flow Rate - Islam, Md Waliul; Hossain, Md Abul; Hooda, Md Nurul; Abedin, Kazi Rafiqul; Ara, Husne (Bangladesh Journal of Urology, 2020)
Objectives: To evaluate urinary symptoms and quality of life in patient with BPH before and after TURP. To determine the impact of TURP on the urinary symptoms (IPSS) and peak urinary flow rate. Methods: This study is prospective study carried out between 2010 and 2011 in the department of Urology, National Institute of Kidney Diseases & Urology. Total 102 cases were selected purposively according to selection criteria. Each patient was observed and followed up at 8 weeks (1st visit), 16 weeks (2nd visit) 24 weeks (3rd visit) after transurethral resection of prostate (TURP). IPSS score, QOL score also recorded and uroflowmetry was done to see the peak urinary flow rate (Qmax) of urine and voiding time. USG was done to see post voidal residual urine volume and DRE also done in selected cases. Data was complied and statistical analysis were done using computer based software, Statistical Package for Social Science (SPSS), using paired ‘t’ test. A P value <0.05 was taken as significance. Results: Before TURP, IPSS range 17-25 and mean 21.61+2.43, after TURP, range 0-7 and mean 4.27+1.71). Hence a significant improvement of IPSS was found from 2 months to 6 months follow up after TURP. The change was tested using “paired student ‘t’ test”. Before TURP Qmax range 7-12.2 and mean was 9.96+1.69, which became range 18-25 and mean was 22.61+2.28 after TURP and therefore change of mean Qmax was 12.64+2.69. The change was tested using “paired student ‘t’ test”. The change was found significant (P<0.001). Conclusion: Transurethral resection of prostate resolves obstructive symptoms, rapid improvement of urinary flow rate Bangladesh Journal of Urology, Vol. 16, No. 1, Jan 2013 p.11-15